Printable graphene BioFETs for DNA quantification in Lab-on-PCB microsystems - Sotirios Papamatthaiou (Nature Portfolio, 2021)
Abstract Lab-on-Chip is a technology that aims to transform the Point-of-Care (PoC) diagnostics field; nonetheless a commercial production compatible technology is yet to be established. Lab-on-Printed Circuit Board (Lab-on-PCB) is currently considered as a promising candidate technology for cost-aware but simultaneously high specification applications, requiring multi-component microsystem implementations, due to its inherent compatibility with electronics and the long-standing industrial manufacturing basis. In this work, we demonstrate the first electrolyte gated field-effect transistor (FET) DNA biosensor implemented on commercially fabricated PCB in a planar layout. Graphene ink was drop-casted to form the transistor channel and PNA probes were immobilized on the graphene channel, enabling label-free DNA detection. It is shown that the sensor can selectively detect the complementary DNA sequence, following a fully inkjet-printing compatible manufacturing process. The results demonstrate the potential for the effortless integration of FET sensors into Lab-on-PCB diagnostic platforms, paving the way for even higher sensitivity quantification than the current Lab-on-PCB state-of-the-art of passive electrode electrochemical sensing. The substitution of such biosensors with our presented FET structures, promises further reduction of the time-to-result in microsystems combining sequential DNA amplification and detection modules to few minutes, since much fewer amplification cycles are required even for low-abundance nucleic acid targets.